GE_GERICHTE C/19680/2015 vom 15. Dezember 2016 - GE Cour de justice (2016)
PROTECTION DE L'UNION CONJUGALE ; DROIT DE GARDE ; RELATIONS PERSONNELLES ; CURATELLE ÉDUCATIVE | CPC.316.3; CPC.311.1; CC.176.3; CC.307.1; CC.308.2; CC.308.3;